Total experimental uncertainty in hydrodynamic testing of a semisubmersible wind turbine, considering numerical propagation of systematic uncertainty. (1st January 2020) - Robertson, Amy; Bachynski, Erin E.; Gueydon, Sebastien; Wendt, Fabian; Schünemann, Paul
Abstract: Quantifying the uncertainty in experimental results is a critical step in properly validating numerical simulation tools for designing floating wind turbines; without a good understanding of the experimental uncertainties, it is impossible to determine if numerical simulation tools can capture the physics with acceptable accuracy. Recent validation studies suggest that the wave-induced, low-frequency surge and pitch motions of semisubmersible-type floating wind turbines are consistently underpredicted by numerical simulations, but it has not been possible to state whether or not this underprediction is within the level of experimental error. In the present work, previously assessed systematic uncertainty components in hydrodynamic tests of the OC5-DeepCwind semisubmersible are propagated to response metrics of interest using numerical simulation tools, and combined with the system's random uncertainty to obtain the total experimental uncertainty. The uncertainty in the low-frequency response metrics is found to be most sensitive to the system properties (e.g., mooring stiffness and center of gravity), and also the wave elevation. The results of the present study suggest that the underprediction of the low-frequency response behavior observed in previous validation studies is larger than the experimental uncertainty. Highlights: Quantification of uncertainty in a floating wind model test campaign. Propagation of uncertainty of input excitation, model properties, and measurements to response metrics of interest. Identification of uncertainty sources with largest impact on response metric uncertainty. Examination of low-frequency response characteristics of a floating semisubmersible. Definition of uncertainty bounds for floating wind model validation.